Hydrogen peroxide in the marine boundary layer over the South Atlantic during the OOMPH cruise in March 2007 - Fischer, H.; Pozzer, A.; Schmitt, T.; Jöckel, P.; Klippel, T.; Taraborrelli, D.; Lelieveld, J. (Atmospheric Chemistry and Physics, 2015)
In the OOMPH (Ocean Organics Modifying Particles in both Hemispheres) project a ship measurement cruise took place in the late austral summer from 01 to 23 March 2007. The French research vessel Marion Dufresne sailed from Punta Arenas, Chile (70.85° W, 53.12° S), to Réunion island (55.36° E, 21.06° S) across the South Atlantic Ocean. In situ measurements of hydrogen peroxide, methylhydroperoxide and ozone were performed and are compared to simulations with the atmospheric chemistry global circulation model EMAC (ECHAM/MESSy Atmospheric Chemistry). The model generally reproduces the measured trace gas levels, but it underestimates hydrogen peroxide mixing ratios at high wind speeds, indicating too-strong dry deposition to the ocean surface. An interesting feature during the cruise is a strong increase of hydrogen peroxide, methylhydroperoxide and ozone shortly after midnight off the west coast of Africa due to an increase in the boundary layer height, leading to downward transport from the free troposphere, which is qualitatively reproduced by the model.